Complement Activation in Trauma Patients Alters Platelet Function. (September 2016) - Atefi, Gelareh; Aisiku, Omozuanvbo; Shapiro, Nathan; Hauser, Carl; Dalle Lucca, Jurandir; Flaumenhaft, Robert; Tsokos, George C.
Abstract : ABSTRACT: Trauma remains the main cause of death for both civilians and those in uniform. Trauma-associated coagulopathy is a complex process involving inflammation, coagulation, and platelet dysfunction. It is unknown whether activation of complement, which occurs invariably in trauma patients, is involved in the expression of trauma-associated coagulopathy. We designed a prospective study in which we enrolled 40 trauma patients and 30 healthy donors upon arrival to the emergency department of BIDMC. Platelets from healthy individuals were incubated with sera from trauma patients and their responsiveness to a thrombin receptor-activating peptide was measured using aggregometry. Complement deposition on platelets from trauma patients was measured by flow cytometry. Normal platelets displayed hypoactivity after incubation with trauma sera even though exposure to trauma sera resulted in increased agonist-induced calcium flux. Depletion of complement from sera further blocked activation of hypoactive platelets. Conversely, complement activation increased aggregation of platelets. Platelets from trauma patients were found to have significantly higher amounts of C3a and C4d on their surface compared with platelets from controls. Depletion of complement (C4d, C3a) reversed the ability of trauma sera to augment agonist-induced calcium flux in donor platelets. Our data indicate that complement enhances platelet aggregation. Despite its complement content, trauma sera render platelets hypoactive and complement depletion further blocks activation of hypoactive platelets. The defect in platelet activation induced by trauma sera is distal to receptor activation since agonist-induced Ca2+ flux is elevated in the presence of trauma sera owing to complement deposition.